Sealing the screw access channel with polytetrafluoroethylene tape: Advantages of the technique - Maluly-Proni, Ana Teresa [UNESP]; Anchieta, Rodolfo Bruniera [UNESP]; Suzuki, Thaís Yumi Umeda [UNESP]; de Oliveira, Fernanda Garcia [UNESP]; Guedes, Ana Paula Albuquerque [UNESP]; Rocha, Eduardo Passos [UNESP]; Assunção, Wirley Gonçalves [UNESP]; dos Santos, Paulo Henrique [UNESP] (Quintessence Publishing, 2017)
The aim of this article is to describe the procedure for sealing the screw access channel using plastic tape, polytetrafluoroethylene, in screw- or cement-retained implant-supported prostheses. This technique is viable and easily performed, and the functional and esthetic results are satisfactory.
Keywords: Cement retention; Dental implants; Implant-supported prosthesis; Polytetrafluoroethylene; Screw retention